Impacto da reflexão estruturada na calibragem diagnóstica de alunos do 6º ano do curso de medicina da Unifenas BH - COSTA FILHO, Galileu Bonifácio da (2017)
Introduction: Diagnostic calibration can be defined as the relationship between diagnostic accuracy and the confidence in that accuracy. Reflective practice seems to be an interesting strategy to improve diagnostic calibration by improving performance insights and has been proposed to foster clinical reasoning by improving diagnostic accuracy. However, its effect on diagnostic calibration has yet to be assessed. Aim: This study seeks to evaluate the impact of structured reflection on diagnostic calibration, diagnostic accuracy, and the confidence in that accuracy while solving dermatology case vignettes. Methods: This study recruited sixth year medical students from Universidad José do Rosário Vellano, who were systematically allocated into one of two groups: reflection group (RG) or control group (CG). Students from both groups were presented the same 12 dermatology cases and were initially asked to point out the probable diagnosis and their confidence in that diagnosis. The students allocated to the RG were then told to reflect on the case using a structured tool. Those allocated to the CG engaged in a time-filler activity before providing their final diagnosis for each case and their final confidence in that diagnosis. Both groups were compared as to their diagnostic accuracy, confidence, and diagnostic calibration overall as well as stratified by dermatological syndrome and case difficulty. Results: Sixty-one students were included (33 in the RG and 28 in the CG). Age and self-assessed perception of knowledge/previous experience were similar in both groups. Gender was significantly different among the groups. Students from the RG showed a better diagnostic accuracy for both melanocytic and non-melanocytic lesions (p=0.025 and p=0.022, respectively). Regarding diagnostic calibration, both RG and CG showed better calibration for melanocytic lesions than for non-melanocytic lesions. Calibration for non-melanocytic lesions was more distant from zero, in a positive direction (i.e. greater overconfidence). It was observed that calibration was worse among more difficult cases, with students showing greater overconfidence when solving such cases. Reflection did not impact significantly on confidence nor on calibration (p=0.228 and p=0.197, respectively). It is worth noting that a significant difference was observed in the calibration in both groups when solving easier cases; students from the RG had a greater diagnostic accuracy, but their confidence did not differ from those in the CG, resulting in an opposite direction of calibration (i.e. among students in the RG, diagnostic accuracy was slightly greater than their confidence). Conclusion: Reflective practice increased the overall diagnostic accuracy, but it did not significantly change overall confidence and calibration. Calibration was worse when solving more difficult cases, and reflection was not enough to improve it.